A rare and interesting case report of Kikuchi-Fujimoto disease masquerading as tuberculosis - Mathew, Joel Danie; K., Ajithakumari; Ninan, Jiby Soosen; Sunny, Juby (International Surgery Journal, 2020)
Kikuchi-Fujimoto disease (KFD), or histiocytic necrotizing lymphadenitis, is a rare benign, self-limited condition, probably genetic, that mainly affects young women which often presents with localised lymphadenopathy and fever. Reporting the case of a 17-year-old girl, with a strong family history of tuberculosis, who presented to the surgery OPD with cervical lymphadenopathy and a history of anti-tubercular treatment for the same complaints two years back. An excision biopsy revealed necrotizing histiocytic lymphadenitis suggestive of KFD. Post-operative period was uneventful and patient had spontaneous resolution of her complaints upon follow up. It is quite difficult to make a pre-operative diagnosis of this disease, until the clinician has got a very high index of suspicion especially because of the more common differential diagnoses including extrapulmonary tuberculosis.